Protein composition of the muscle mitochondrial reticulum during postnatal development. (8th April 2019) - Kim, Yuho; Yang, Daniel S.; Katti, Prasanna; Glancy, Brian
Abstract : Key points: Muscle mitochondrial networks changed from a longitudinal, fibre parallel orientation to a perpendicular configuration during postnatal development. Mitochondrial dynamics, mitophagy and calcium uptake proteins were abundant during early postnatal development. Mitochondrial biogenesis and oxidative phosphorylation proteins were upregulated throughout muscle development. Postnatal muscle mitochondrial network formation is accompanied by a change in protein expression profile from mitochondria designed for co‐ordinated cellular assembly to mitochondria highly specialized for cellular energy metabolism. Abstract: Striated muscle mitochondria form connected networks capable of rapid cellular energy distribution. However, the mitochondrial reticulum is not formed at birth and the mechanisms driving network development remain unclear. In the present study, we aimed to establish the network formation timecourse and protein expression profile during postnatal development of the murine muscle mitochondrial reticulum. Two‐photon microscopy was used to observe mitochondrial network orientation in tibialis anterior (TA) muscles of live mice at postnatal days (P) 1, 7, 14, 21 and 42, respectively. All muscle fibres maintained a longitudinal, fibre parallel mitochondrial network orientation early in development (P1–7). Mixed networks were most common at P14 but, by P21, almost all fibres had developed the perpendicular mitochondrial orientation observed in mature, glycolytic fibres. Tandem mass tag proteomics were then applied to examine changes in 6869 protein abundances in developing TA muscles. Mitochondrial proteins increased by 32% from P1 to P42. In addition, both nuclear‐ and mitochondrial‐DNA encoded oxidative phosphorylation (OxPhos) components were increased during development, whereas OxPhos assembly factors decreased. Although mitochondrial dynamics and mitophagy were induced at P1–7, mitochondrial biogenesis was enhanced after P14. Moreover, calcium signalling proteins and the mitochondrial calcium uniporter had the highest expression early in postnatal development. In conclusion, mitochondrial networks transform from a fibre parallel to perpendicular orientation during the second and third weeks after birth in murine glycolytic skeletal muscle. This structural transition is accompanied by a change in protein expression profile from mitochondria designed for co‐ordinated cellular assembly to mitochondria highly specialized for cellular energy metabolism. Key points: Muscle mitochondrial networks changed from a longitudinal, fibre parallel orientation to a perpendicular configuration during postnatal development. Mitochondrial dynamics, mitophagy and calcium uptake proteins were abundant during early postnatal development. Mitochondrial biogenesis and oxidative phosphorylation proteins were upregulated throughout muscle development. Postnatal muscle mitochondrial network formation is accompanied by a change in protein expression profile from mitochondria designed for co‐ordinated cellular assembly to mitochondria highly specialized for cellular energy metabolism.